Struktur Komunitas Moluska pada Musim Barat dan Musim Peralihan I di Perairan Tanjung Benoa Badung, Bali - Astiti, Dewa Ayu Wedha; Faiqoh, Elok; Putra, I Nyoman Giri (Journal of Marine and Aquatic Sciences, 2021)
Tanjung Benoa is a waters in Bali that is influenced by the monsoon pattern system which has a different circulation pattern of water masses and varies between seasons. The difference in mass of water resulted in changes in the condition of the waters that affect the high and low productivity of the waters and abundance of mollusks in the waters of Tanjung Benoa. Mollusks have an important role for the aquatic environment, namely as a bio-indicator of environmental health and water quality. This study aims to determine the structure of the molluscs community and determine the environmental factors that influence the western season and the transition season I. Sampling is done in January 2019 (west season) and in March 2019 (Transition I). The results of the analysis showed a decrease in diversity and uniformity occurred in the fourth week (west season) and the seventh week (transition season I) with the category of moderate species diversity and medium type uniformity. The low value of uniformity and diversity in the western season is influenced by increasing pH values and decreasing waters nitrate values. When compared with the western season, in the transition season I the increase in temperature and a decrease in phosphate value occur in the seventh week. this result was obtained using principal component analysis (PCA) that used the environmental parameter index and the value of diversity and uniformity of mollusks. However, this value is still in the medium category. So it can be seen in the western season and the transition season. The state of mollusks in Tanjung Benoa waters is stable and can adapt to seasonal changes and environmental conditions.